The crime of homosexuality in Iraqi legislation - Adnan Yali, Researcher. Huda; Hanoun Khalaf, Prof. Dr. Ghazi (Basra studies journal, 2024)
Homosexuality is one of the serious issues facing humanity today. It is no longer just an expression of personal preferences or attraction towards the same sex, nor is it merely a moral deviation. It has become an attempt to negate the human existence represented by male and female, the binary that forms the cornerstone of building society. This poses a serious threat to human existence, in addition to undermining social and moral values in society, making homosexuality a globally recognized phenomenon. Legislation has sought to protect individuals' personal freedoms, including sexual freedom, by stipulating that these freedoms must be exercised within legal and religious frameworks to protect dignity and public decency. Therefore, rules have been established to regulate various sexual behaviors, including homosexuality, so as not to conflict with moral, religious, cultural norms, and traditions prevailing in society. Regulating sexual instincts through legal rules ensures that they are directed in the right path, fulfilling their function in preserving gender and the continuity of the human race. However, if these instincts deviate from their function and pursue aberrant goals and objectives, they become a dangerous evil that must be prevented and mitigated.